2020
DOI: 10.3390/pr8010096
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Cs–Pollucite Nanozeolite Modified with Novel Organosilane as an Excellent Solid Base Catalyst for Claisen–Schmidt Condensation of Benzaldehyde and Acetophenone

Abstract: Cs–pollucite can be a potential solid base catalyst due to the presence of (Si-O-Al)−Cs+ basic sites. However, it severely suffers from molecular diffusion and pore accessibility problems due to its small micropore opening. Herein, we report the use of new organosilane, viz. dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride (TPOAC), as a promising pore-expanding agent to develop the hierarchical structure in nanosized Cs–pollucite. In respect to this, four different amounts of TPOAC were added duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…7b). 50 As a result, high specific BET surface area is shown by SAPO-34 (393 m 2 g −1 ) as compared to SAPO-20 (29 m 2 g −1 ) (Table 2). Furthermore, the Non-local Density Functional Theory (NLDFT) method also reveals that SAPO-34 has a larger average pore size (3.26 nm) due to its primary micro- and textural mesoporosities.…”
Section: Resultsmentioning
confidence: 96%
“…7b). 50 As a result, high specific BET surface area is shown by SAPO-34 (393 m 2 g −1 ) as compared to SAPO-20 (29 m 2 g −1 ) (Table 2). Furthermore, the Non-local Density Functional Theory (NLDFT) method also reveals that SAPO-34 has a larger average pore size (3.26 nm) due to its primary micro- and textural mesoporosities.…”
Section: Resultsmentioning
confidence: 96%
“…Later, to increase the yield, different catalysts were also tried [ 58 , 59 ]. For example, materials such as chitosan [ 60 ], Al–Mg hydrotalcite [ 61 ], and Cs-pollucite nanozeolite modified with organosilane [ 62 ] have been used for the reaction. The acid-based catalyst, i.e., BF 3 -Et 2 O, has many advantages over others, with the yield of the chalcone increasing drastically, which is also helpful for the ease of production [ 2 ].…”
Section: Synthesis Of Chalconesmentioning
confidence: 99%
“…On the other hand, the total surface area of the samples was measured with the N 2 adsorption isotherm analysis. Note that the total surface area determined was actually contributed only by the external surfaces because the size of N 2 molecules is too large to probe the micropores of the K-MER zeolite [27,37]. The results indicated that the external surface area had positive correlation with the crystallite size of K-MER zeolite.…”
Section: Morphological Effects On the Catalytic Behavior Of K-mer Zeomentioning
confidence: 99%